RESEARCH ON LIU ERXIN WITH EDUCATION AND INDUSTRY UNDERTAKINGS IN MODERN GANSU (Conferencea, 2023)
As a famous scholar, educator and industrialist in modern Gansu, Liu Erxin was not fond of chasing fame, but devoted himself to education and industry careers all his life, and made significant contributions to the development of education and social welfare in Gansu. On the basis of collecting relevant historical materials earnestly, this article briefly introduces the general situation of cultural geography in Gansu, focuses on analyzing Liu Erxin’s life experience and academic achievements, and objectively excavates Liu Erxin’s major accomplishments in the aspect of education and industry, with a view to providing some scientific research achievements for the research of modern Gansu regional culture and some historical materials of celebrities.